A view on systematic truncation of tetrahedral ligands for coordination polymers. Issue 5 (17th January 2017) - Zhao, Tian; Heering, Christian; Boldog, Ishtvan; Domasevitch, Konstantin V.; Janiak, Christoph
Abstract : Bis-, tris- and tetrakis(carboxyphenyl)adamantanes were probed for the synthesis of coordination polymers of d-metals, with successful outcome for Mn, Co, Cd. Formation ofsqI, hcb anddia frameworks based on small clusters demonstrates the dominant role of the ligand shape in defining the outcome of crystallization Abstract : Bis-, tris- and tetrakis(carboxyphenyl)adamantanes were probed for the synthesis of coordination polymers of d-metals, with a successful outcome for Mn, Co, and Cd. Formation ofsql, hcb anddia frameworks based on small clusters demonstrates the dominant role of the ligand shape in defining the outcome of crystallization.